From Ideality to Simplicity: A Robust and Affordable Hydrogen Reference Electrode - Durán Chaves, Michelle (2020)
In electrochemistry, the concept of a reference electrode is fundamental. Introductory courses might mention the standard hydrogen electrode (SHE), its working principle, and its theoretical design; however, chances are that students will never have the opportunity to work with one. A hydrogen electrode should be a device readily available at the laboratory, either from an academic or an experimental point of view. The construction of a simple, robust hydrogen reference electrode, with materials available at the laboratory, is proposed. The main purpose is to fulfill the desired characteristics in a reference electrode such as stable potential over time, mechanical stability, and low cost. The designed robust hydrogen reference electrode (RHRE) presented adequate potential stability. Electrochemical characterization indicates that the RHRE is an acceptable system for electrochemical measurements. From an academic point of view, this electrode could be used as a practical tool for the learning process of the hydrogen electrode operation.